Education policy and equality of opportunity - Ludger Woessmann; Heinrich W. Ursprung; Gabriela Schuetz (Center for Economic Studies and ifo Institute (CESifo), 2005)
We provide a measure of equality of educational opportunity in 54 countries, estimated as the effect of family background on student performance in two international TIMSS tests. We then show how organizational features of the education system affect equality of educational opportunity. Our model predicts that late tracking and a long pre-school cycle are beneficial for equality, while pre-school enrollment is detrimental at low levels of enrollment and beneficial at higher levels. Using cross-country variations in education policies and their interaction with family background at the student level, we provide empirical evidence supportive of these predictions.
Keywords: I21; H52; J62; 330; equality of opportunity; educational production; family background; student performance; tracking; pre-school; efficiency-equity tradeoff; Bildungschancen; Bildungsniveau; Familiensoziologie; Bildungspolitik; Bildungsökonomik; Schätzung; Welt